2018
DOI: 10.1109/jlt.2017.2776297
|View full text |Cite
|
Sign up to set email alerts
|

In-Line Mach-Zehnder Interferometer With D-Shaped Fiber Grating for Temperature-Discriminated Directional Curvature Measurement

Abstract: A high-sensitivity curvature sensing configuration is implemented by using a fiber Mach-Zehnder interferometer (MZI) with D-shaped fiber Bragg grating (FBG). A segment of D-shaped fiber is fusion spliced into a single mode fiber at both sides, and then a short FBG is inscribed in the D-shaped fiber. The fiber device yields a significant spectrum sensitivity as high as 87.7 nm/m-1 to the ultra-low curvature range from 0 to 0.3 m-1 , and can distinguish the orientation of curvature experienced by the fiber as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 22 publications
(29 reference statements)
0
18
0
Order By: Relevance
“…Jiang et al demonstrated a sensor for simultaneous measurement of temperature and directional curvature based on the composition of an MZI and an FBG inscribed in a segment of the D‐shaped optical fiber by a UV laser. And two ends of the D‐shaped optical fiber were spliced with SMFs with core‐offset, which were used as the beam splitter and beam combiner.…”
Section: D‐shaped Fiber Grating Sensorsmentioning
confidence: 99%
“…Jiang et al demonstrated a sensor for simultaneous measurement of temperature and directional curvature based on the composition of an MZI and an FBG inscribed in a segment of the D‐shaped optical fiber by a UV laser. And two ends of the D‐shaped optical fiber were spliced with SMFs with core‐offset, which were used as the beam splitter and beam combiner.…”
Section: D‐shaped Fiber Grating Sensorsmentioning
confidence: 99%
“…Here, we inserted a small segment of asymmetrical D-shaped fiber to construct the MZI, as shown in Fig. 2(a), which promises sensitive wavelength responses and broader tuning on the mechanical strain, bending and temperature [20]. The inset shows the cross-section of the employed D-shaped fiber with the asymmetric structure, the fiber core with a diameter of 9.57 μm is placed at a distance of 3.55 μm from the flat surface.…”
Section: Device Fabricationmentioning
confidence: 99%
“…The prepared MZI structure was firstly hydrogenated for photosensitivity enhancement, and then a FBG was UV-inscribed into the D-shaped fiber by using the scanning phase-mask technique and a frequency-doubled continuous wave argon-ion laser [20], [21]. During the inscription, the flat surface of D-shaped fiber is rotated to face the phase mask and UV-laser, avoiding the asymmetric edge diffraction for an improvement of the inscription efficiency.…”
Section: Device Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, nontrivial modification and precise alignment of grating writing tools are required in such processing such structures. Finally, several other vector bending schemes have also been investigated with FBGs in and eccentric-core [31] and D-shaped fibers [32], for which low loss splicing to standard single mode fiber (SMF) is difficult.…”
Section: Introductionmentioning
confidence: 99%